2022
DOI: 10.1590/1984-0462/2022/40/2020407
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sleep characteristics of children and adolescents with type 1 diabetes mellitus

Abstract: Objective: To evaluate sleep characteristics of children and adolescents with type 1 diabetes mellitus (T1DM) and their relationship with glycemic control. Methods: A cross-sectional study was conducted at a public hospital in São Paulo, Brazil. It included 86 patients with T1DM, aged between 10 and 18 years old, who were on insulin therapy, had performed at least three measurements of capillary blood glucose throughout the day, and had normal thyroid function. The clinical, anthropometric, and laboratory dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
3
0
2
Order By: Relevance
“…Previous research has supported these findings, as our recent meta-analysis showed that social jet lag was significantly associated with higher BMI, waist circumference, HbA1c levels, and systolic blood pressure in general but also in people with diabetes [7]. This is also in agreement with findings in people with type 1 diabetes [8][9][10][11]. In this study, however, we only found cross-sectional associations among social jet lag and markers of glycemic and metabolic control, and not prospectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous research has supported these findings, as our recent meta-analysis showed that social jet lag was significantly associated with higher BMI, waist circumference, HbA1c levels, and systolic blood pressure in general but also in people with diabetes [7]. This is also in agreement with findings in people with type 1 diabetes [8][9][10][11]. In this study, however, we only found cross-sectional associations among social jet lag and markers of glycemic and metabolic control, and not prospectively.…”
Section: Discussionsupporting
confidence: 92%
“…Our recent meta-analysis of the associations among social jet lag and parameters of the metabolic syndrome and T2D has shown that social jet lag is associated with increased levels of glycated hemoglobin (HbA1c), higher body mass index (BMI), higher waist circumference, and higher odds of obesity [7]. Social jet lag has also been associated with worse glycemic control, higher HbA1c levels, and higher insulin requirements in people with type 1 diabetes [8][9][10][11]. Few studies have assessed the effects of social jet lag in people with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, no violations of the null hypothesis were found for the sleep assessment variables according to age and gender. Similar results were found in a study of children and adolescents aged between 10 and 18 with type I diabetes mellitus, for whom age and gender were not predictors of a greater chance of daytime sleepiness (21) . There are also compatible results with children and adolescents with cancer, and age was also not a predictor of shorter sleep duration (6) .…”
Section: Discussionsupporting
confidence: 85%
“…In children and adolescents with type I diabetes mellitus, there was a higher prevalence of daytime sleepiness among patients with a diagnosis of less than 3 years when compared to those with a diagnosis of 3 years or more (57.1% versus 36.2%; p = 0.03). However, insulin treatment had no influence on daytime sleepiness (p = 0.80) (21) .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation